Pesquisa das espécies e sensibilidade antifúngica de Candida sp. em indivíduos soropositivos para o HIV - Atique, Tábata Salum Calille (2006)
Oropharyngeal candidiasis is the commonest infection among HIV-infected individuals and the most frequently isolated agent is Candida albicans. However, other species have had significant increase, some of these presenting distinguishing susceptibility or total unresponsive to the antifungical drugs, in special to fluconazole. Objective: To determine the prevalence of Candida sp. in the oropharyngeal cavity of a HIV-infected/AIDS population and of its control group, with emphasis in C. dubliniensis study. Furthermore, our objective was to assess the antifungical susceptibility profiles of the isolated strains. Methods: The sample collection was realized through a sterile swab and posterior isolation on agar Sabouraud Dextrose® and BBL Mycosel Agar®. Colonies which resembled Candida were replaced in CHROMagar Candida® media. Afterwards, accordingly to their colours and/or tonalities the distinct colonies were submitted to the following identification tests: chlamydospore production on corn meal agar with Tween 80; germinative tube formation and biochemical profile analysis. The green colonies were also submitted to specific tests for phenotypic selection of C. dubliniensis: tolerance to 42 and 45 degrees temperature to C and 6,5% hypertonic agar, chlamydospore formation on Sunflower Seed agar and Niger agar, by the formation of an opacity halo in agar with Tween 80 and D-xylose and alpha D-glucopiranoside assimilation. Finally, the antifungical susceptibility profiles were evaluated by disk diffusion and microdilution. Results: In patients, the prevalence of colonization/infection was of 87%, being a total of 107 strains there isolation. From these, seventy-six were identified as C. albicans, whereas non-albicans: 18 as C. tropicalis, 10 as C. glabrata and three of them as C. dubliniensis. In addition, from the obtained material though the oropharyngeal cavity of 20 patients, was possible the isolation of more than one species of Candida sp., characterizing mixed colonization and/or infection. On the other hand, from the individuals of the control group, this prevalence was much smaller (9%) and the totality of the isolated strains was typed as C. albicans. The isolated strains from the patients were significantly more resistant to fluconazole (p= 0,0039) than those isolated from the oropharyngeal cavity of the controls. Conclusions: The prevalence of Candida sp., considering C. albicans and non-albicans in the HIV serumpositive/AIDS patients is high. C. dubliniensis prevalence is similar to that one those reported in other regions of Brazil. C. albicans was the only isolated species of the oropharyngeal cavity of the control group individuals. The isolated strains from patients oral cavity s are more resistant to antifungical drugs than those isolated in the same anatomical site in the control group. Finally, non-albicans species are more resistant to the azoles and amphotericin B than C. albicans.